2006
DOI: 10.1103/physrevlett.96.039602
|View full text |Cite
|
Sign up to set email alerts
|

Diebel and Dunham Reply:

Abstract: Diebel and Dunham Reply: Fiorentini and Lopez [1] have identified a lower energy structure for the F 4 V complex than the higher symmetry structure which we considered in Ref. [2]. Our calculations using the methods described in Ref.[2] confirm the lower energy of this structure. By exploring a range of configurations, we also found lower energy structures for F 3 V, F 4 V 2 , F 5 V 2 , and F 6 V 2 . The energy differences are most significant for higher F to V ratios, and these F n V m structures have rotated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 5 publications
7
36
0
2
Order By: Relevance
“…[22][23][24] We also carried out some calculations for F n V m clusters in Si and found binding energy values that were very similar to those reported previously. 13,14 For example, our predicted binding energy of the FV pair in Si is Ϫ2.23 eV, which is in excellent agreement with the DFT study of Lopez et al 14 ͑Ϫ2.0 eV͒ and the experimental value of Pi et al 9 ͑Ϫ2.2 eV͒.…”
Section: Theoretical Methodologysupporting
confidence: 79%
See 2 more Smart Citations
“…[22][23][24] We also carried out some calculations for F n V m clusters in Si and found binding energy values that were very similar to those reported previously. 13,14 For example, our predicted binding energy of the FV pair in Si is Ϫ2.23 eV, which is in excellent agreement with the DFT study of Lopez et al 14 ͑Ϫ2.0 eV͒ and the experimental value of Pi et al 9 ͑Ϫ2.2 eV͒.…”
Section: Theoretical Methodologysupporting
confidence: 79%
“…These predictions agree with previous results for F interstitials in Si. 13,14 As the bond-center F interstitials are positively charged, they should repel each other, whereas the tetrahedral F interstitials should repel each other because they are negatively charged. Conversely, F interstitial pairs consisting of a bondcenter and a tetrahedral interstitial should be bound ͑F 2 ͒.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, it is known that the slowing down of boron TED occurs by the interaction between F and point defects, and it has been suggested that F atoms form complexes with these defects. [3][4][5][6][7][8][9] By ab initio calculations, several authors 5,7,8,10 have found that the lowest-energy state for a single interstitial F in Si is at the bond-centered the ͑BC͒ site in the +1 charge state or at the tetrahedral ͑T͒ site in the −1 charge state, depending on the Fermi energy. However, in Refs.…”
mentioning
confidence: 99%
“…In the RIE process, structural defects such as fluorinevacancy complexes are formed by penetrating fluorine into silicon lattice at or near the surface structure. [16][17][18][19][20] The defects created and the high concentration of fluorine impurity as detected by XPS can modify surface states by introducing impurity states in the bandgap. Hence, the surface of the nanocones can be considered as an absorber for photons which has energy lower than the bandgap energy.…”
Section: -2mentioning
confidence: 99%